-6(3h+9)=-22

Simple and best practice solution for -6(3h+9)=-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(3h+9)=-22 equation:


Simplifying
-6(3h + 9) = -22

Reorder the terms:
-6(9 + 3h) = -22
(9 * -6 + 3h * -6) = -22
(-54 + -18h) = -22

Solving
-54 + -18h = -22

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '54' to each side of the equation.
-54 + 54 + -18h = -22 + 54

Combine like terms: -54 + 54 = 0
0 + -18h = -22 + 54
-18h = -22 + 54

Combine like terms: -22 + 54 = 32
-18h = 32

Divide each side by '-18'.
h = -1.777777778

Simplifying
h = -1.777777778

See similar equations:

| Y/4-7=-3 | | X-3/2=4/8 | | 3(4n+7)=-32 | | 20-n=37 | | 4x1/2=8 | | 60b^2+31b-3=0 | | x^2-34x-273=0 | | 4.75x+2y=3.45 | | -10-a=-15 | | (3+i)(-4+3i)= | | -10-a=15 | | 5a-6-2a=1/ | | P/3-7=14 | | x^2-32x-273=0 | | -k/4-3=10 | | 4a=3.2 | | 6x+4(-3+1x)=13 | | -12=-4/5x | | 6a=6.6 | | 5p+6=4-8 | | 2y=2.2 | | -8+12=2x+11 | | y^2-34y-273=0 | | 2x^3-10x-1=0 | | X+28+(6x+5)+39=180 | | 17x^3-10x-1=0 | | G*2=30-7g | | 5w-7(0.5w+8)=-7(3+w) | | y=15x-9 | | 5/8j=-1 | | 5p(3-5)=-4(6-p) | | 40x+7.5x=865.38 |

Equations solver categories